Mining High-Efficiency Itemsets with Negative Utilities - Irfan Yildirim (Mathematics, 2025)
High-efficiency itemset mining has recently emerged as a new problem in itemset mining. An itemset is classified as a high-efficiency itemset if its utility-to-investment ratio meets or exceeds a specified efficiency threshold. The goal is to discover all high-efficiency itemsets in a given database. However, solving the problem is computationally complex, due to the large search space involved. To effectively address this problem, several algorithms have been proposed that assume that databases contain only positive utilities. However, real-world databases often contain negative utilities. When the existing algorithms are applied to such databases, they fail to discover the complete set of itemsets, due to their limitations in handling negative utilities. This study proposes a novel algorithm, MHEINU (mining high-efficiency itemset with negative utilities), designed to correctly mine a complete set of high-efficiency itemsets from databases that also contain negative utilities. MHEINU introduces two upper-bounds to efficiently and safely reduce the search space. Additionally, it features a list-based data structure to streamline the mining process and minimize costly database scans. Experimental results on various datasets containing negative utilities showed that MHEINU effectively discovered the complete set of high-efficiency itemsets, performing well in terms of runtime, number of join operations, and memory usage. Additionally, MHEINU demonstrated good scalability, making it suitable for large-scale datasets.